2023
DOI: 10.3389/fenvs.2023.976113
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the active carbonyl groups and residual acid on the ammonia adsorption over the acid-modified activated carbon

Abstract: 2023), The effect of the active carbonyl groups and residual acid on the ammonia adsorption over the acid-modified activated carbon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…For instance, Zheng et al [ 83 ] developed fiber-form AC modified by acidic oxygen groups, which exhibited a high NH 3 adsorption capacity of 50 mg g −1 . Li et al [ 84 ] found that AC modified by HNO 3 exhibited the best NH 3 removal performance among three inorganic acid-modified ACs, with a maximum NH 3 adsorption amount of 40 mg g −1 , owing to the reduced adsorption energy caused by the co-adsorption of NH 3 with residual HNO 3 via a hydrogen bond network. More recently, Zhang et al [ 85 ] demonstrated that ordered MS functionalized with a sulfonic group (OMS-SO 3 H) exhibited ultra-high precision for NH 3 reversible adsorption and separation, benefiting from the high density of –SO 3 H superic acid sites in ordered mesochannels.…”
Section: Porous Solids For Nh 3 Adsorptionmentioning
confidence: 99%
“…For instance, Zheng et al [ 83 ] developed fiber-form AC modified by acidic oxygen groups, which exhibited a high NH 3 adsorption capacity of 50 mg g −1 . Li et al [ 84 ] found that AC modified by HNO 3 exhibited the best NH 3 removal performance among three inorganic acid-modified ACs, with a maximum NH 3 adsorption amount of 40 mg g −1 , owing to the reduced adsorption energy caused by the co-adsorption of NH 3 with residual HNO 3 via a hydrogen bond network. More recently, Zhang et al [ 85 ] demonstrated that ordered MS functionalized with a sulfonic group (OMS-SO 3 H) exhibited ultra-high precision for NH 3 reversible adsorption and separation, benefiting from the high density of –SO 3 H superic acid sites in ordered mesochannels.…”
Section: Porous Solids For Nh 3 Adsorptionmentioning
confidence: 99%
“…The choice of the adsorbent plays a critical role in the process. Various adsorbent materials, including carbon-based adsorbents, alumina, silica, , and metal-organic frameworks (MOFs), ,, have been developed and modified to functionalized surfaces and porous structures, allowing for effective removal of NH 3 . For instance, Wang et al used the MOF MIL-53-(OH) 2 as a base material and incorporated lithium chloride within its nanopore channels to achieve high-performance heterogeneous MOF adsorbents for NH 3 capture.…”
Section: Introductionmentioning
confidence: 99%